Agriculture in Poland and Ukraine – Potential and Dynamics of Changes in Production - Ludwik Wicki; Mykola Orlykovskyi; Lesia Zaburanna (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The article attempts to compare the importance of agriculture and the dynamics of its development in Ukraine and Poland. The most important constraints on the development of Ukrainian agriculture were identified, including the unregulated land market, lack of coherent support programs for agriculture and rural areas, poorly developed infrastructure of the agricultural environment and lack of capital for development. It was found that agriculture in Ukraine is characterized by a high growth rate of productivity and production. The observed output gap in relation to agriculture in Poland is about 10 years. The agricultural sector in Ukraine has about 10% share in generating GDP and as much as 40% share in exports. Such high importance can be maintained even in the conditions of economic development, as there are large reserves in the development of agribusiness. The most important development factors include the introduction of a coherent program for the development of the agribusiness sector, including production of goods with high added value and increasing the availability of capital for the development of agriculture. A great opportunity is the development of trade in the conditions of affiliation with the EU.